Status of Logistics and Transport Infrastructure Development Directions in Uzbekistan - Samiyeva G. T.; Tinicheva M. G. (Research Parks Publishers, 2022)
This article presents new information on the development of logistics and transport infrastructure in our country. A number of guidelines have been issued for the development of logistics, transport infrastructure and the strengthening of international relations.